Immune Reconstitution after Allogeneic Hematopoietic Stem Cell Transplantation - Ogonek, Justyna; Kralj Juric, Mateja; Ghimire, Sakhila; Varanasi, Pavankumar Reddy; Holler, Ernst; Greinix, Hildegard; Weissinger, Eva (Frontiers in Immunology, 2016)
The reconstitution and the regaining of function of a healthy, transplanted immune system is of utmost importance for the recovery and long term survival of patients after HSCT. New developments within HSCT, for example, umbilical cord blood or haploidentical grafts, both leading to prolonged immunodeficiency and delayed immune reconstitution, have increased the need to improve immune reconstitution. Thus, understanding and enhancing immune reconstitution post-HSCT is an area of intense research. Immune reconstitution post-HSCT occurs in several steps, innate immunity being the first to regain function. Although the slow T-cell reconstitution is regarded as primarily responsible for deleterious infections with latent viruses or fungi, occurrence of graft-versus-host disease, and relapse, the importance of innate immune cells for disease and infection control is being reevaluated. Here we aim to summarize the major steps of the immune reconstitution in patients after HSCT.